Platelets and Immature Neutrophils in Preterm Infants with Feeding Intolerance - Alhamad, Moath M.A.; Kumar, Ambuj; Chaaban, Hala; Wickline, Karen M.; Ho, Thao T.B. (American Journal of Perinatology, 2020)
Objective Feeding intolerance (FI) is a common presentation of necrotizing enterocolitis (NEC) and sepsis. NEC and sepsis are associated with hematological changes, but these changes alone are not reliable biomarkers for early diagnosis. This study examined whether the combination of hematological indices and FI can be used as an early diagnostic tool for NEC or sepsis.Study Design This retrospective cohort study included infants born at <1,500 g or <30 weeks who had symptoms of FI. The exclusion criteria were congenital or chromosomal disorders, thrombocytopenia or platelet transfusion before the onset of FI, and history of bowel resection. We compared the hematological indices from infants with pathologic FI (due to NEC or sepsis) to infants with benign FI.Results During the study period, 211 infants developed FI; 185 met the inclusion criteria. Infants with pathologic FI (n = 90, 37 cases with NEC and 53 with sepsis) had lower birth gestational age and weight compared with 95 infants with benign FI (n = 95). Pathologic FI was associated with lower platelet count (median 152 × 103/μL vs. 285 × 103/μL, p < 0.001) and higher immature-to-total neutrophil (I/T) ratio (median 0.23 vs. 0.04, p < 0.001) at the onset of FI. Pathologic FI was also associated with a decrease in baseline platelets compared with an increase in benign FI. For diagnosis of pathologic FI, a decrease ≥10% in platelets from baseline had a sensitivity and specificity of 0.64 and 0.73, respectively, I/T ratio ≥0.1 had a sensitivity and specificity of 0.71 and 0.78, respectively, and the combination of both parameters had a sensitivity and specificity of 0.50 and 0.97, respectively.Conclusion FI caused by NEC or sepsis was associated with a decrease in platelets from baseline, and a lower platelet level and higher I/T ratio at the onset of FI. These findings can help clinicians in the management of preterm infants with FI.Key Points
Keywords: prematurity; necrotizing enterocolitis; sepsis; feeding intolerance; platelets; neutrophils